(untitled) (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To determine the spectrum of injuries with fodder cutter (toka) machines and which sex is more prone to these injuries in southern Punjab. Methods: Total 73 patients were included in this interventional study. All the patients with toka machine injuries of either sex presenting in emergency department during fifteen months from Jan 2014 to March 2015 were included in the study. Results: Male patients were 32 (44%), Female and children involvement in such injuries was 41(56%). Upper limb was involved in 69 patients and bilateral limbs in 04 patients. Conclusion: Toka machine injuries are very common that leads to morbidity, disability and often mortality. Victims were usually females, male and children, so the awareness campaigns regarding hazards and safety measures in using agricultural machine should be launched at national level. Key words: Toka machine injury, female and children, traumatic amputation upper limb.